2018
DOI: 10.1111/ijd.14353
|View full text |Cite
|
Sign up to set email alerts
|

Systemic comorbidities associated with rosacea: a multicentric retrospective observational study

Abstract: Background Once considered a disorder limited to the skin, rosacea is now known to be associated with systemic disorders. The aim of this study was to determine what systemic comorbidities accompany rosacea and to determine the relationship between the type, severity, and duration of rosacea, and the presence of and type of systemic comorbidities. Methods This retrospective multicenter study was conducted by the Turkish Society of Dermatology Acne Study Group. Thirteen dermatology clinics throughout Turkey par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 20 publications
3
27
1
Order By: Relevance
“…A strong association between rosacea and metabolic disorder (i.e., diabetes mellitus and obesity) has been recognized in prior studies [ 47 , 48 ] and ours. It is postulated that systemic inflammation underlying rosacea induces structural changes of the lipoprotein, which adversely affects the lipid profile [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 75%
“…A strong association between rosacea and metabolic disorder (i.e., diabetes mellitus and obesity) has been recognized in prior studies [ 47 , 48 ] and ours. It is postulated that systemic inflammation underlying rosacea induces structural changes of the lipoprotein, which adversely affects the lipid profile [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 75%
“…also suggested that rosacea may be a risk factor for breast cancer in independent epidemiological studies. A recent report in Turkish showed that rosacea was significantly associated with respiratory tract, gastrointestinal system, metabolic and hepatobiliary diseases …”
Section: Introductionmentioning
confidence: 99%
“…A recent report in Turkish showed that rosacea was significantly associated with respiratory tract, gastrointestinal system, metabolic and hepatobiliary diseases. 33 However, the association between rosacea and cancers in the Chinese population remains unclear. In this study, we conducted a cross-sectional study to examine the association between rosacea and selected cancers in a medical center in southern China, and we further explore potential related factors.…”
Section: Introductionmentioning
confidence: 99%
“…Because rosacea patients demonstrate a significantly higher prevalence of small intestinal bacterial overgrowth than controls, a connection between gut dysbiosis, skin dysbiosis, and the development of rosacea has been proposed . While there are many studies investigating the role of the gut microbiota in systemic disorders, studies of the skin microbiota are lacking.…”
mentioning
confidence: 99%
“…Because rosacea patients demonstrate a significantly higher prevalence of small intestinal bacterial overgrowth than controls, a connection between gut dysbiosis, skin dysbiosis, and the development of rosacea has been proposed. 1 While there are many studies investigating the role of the gut microbiota in systemic disorders, studies of the skin microbiota are lacking. In our recent study of the microbiota of the facial skin in papulopustular rosacea (PPR) and erythematotelangiectatic rosacea (ETR), we identified a number of bacterial taxa that are enriched or depleted in individuals with rosacea compared to matched controls.…”
mentioning
confidence: 99%